2012
DOI: 10.1108/15736101211269122
|View full text |Cite
|
Sign up to set email alerts
|

Computational investigation of shock‐mitigation efficacy of polyurea when used in a combat helmet

Abstract: Purpose -Polyurea falls into a category of elastomeric co-polymers in which, due to the presence of strong hydrogen bonding, the microstructure is of a heterogeneous nature and consists of a compliant/soft matrix and stiff/hard nanometer size hard domains. Recent investigations have shown that the use of polyurea as an external or internal coating/lining had substantially improved ballistic-penetration resistance of metallic structures. The present work aims to use computational methods and tools in order to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 22 publications
2
26
0
Order By: Relevance
“…The peak ICPs obtained from our head model were slightly higher than those reported by Tan et al due to their inclusion of foam paddings within the helmets while the current model used the strap suspension system. Extra padding had been reported to mitigate the blast wave effects on the head . Even though the head and helmet models may be different, comparison of our results with the published values showed that similar magnitudes of ICPs were obtained, and hence ascertain the appropriate modelling methodology used.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The peak ICPs obtained from our head model were slightly higher than those reported by Tan et al due to their inclusion of foam paddings within the helmets while the current model used the strap suspension system. Extra padding had been reported to mitigate the blast wave effects on the head . Even though the head and helmet models may be different, comparison of our results with the published values showed that similar magnitudes of ICPs were obtained, and hence ascertain the appropriate modelling methodology used.…”
Section: Resultssupporting
confidence: 70%
“…Extra padding had been reported to mitigate the blast wave effects on the head. 46,47 Even though the head and helmet models may be different, comparison of our results with the published values showed that similar magnitudes of ICPs were obtained, and hence ascertain the appropriate modelling methodology used.…”
Section: Analysis Landmarkssupporting
confidence: 75%
“…This class of elastomer has gained a lot of interest by both academia and industry in the last few years, in view of their ability to exhibit a range of mechanical properties, which in turn is an indirect manifestation of its composite microstructure . Polyurea is finding interesting applications in specialized fields, especially as linings in personnel‐protective gear, retrofits for unreinforced structures, and as ballistic‐penetration resistant metallic armor …”
Section: Introductionmentioning
confidence: 99%
“…1 This class of elastomer has gained a lot of interest by both academia and industry in the last few years, in view of their ability to exhibit a range of mechanical properties, which in turn is an indirect manifestation of its composite microstructure. [2][3][4] Polyurea is finding interesting applications in specialized fields, especially as linings in personnel-protective gear, 5 retrofits for unreinforced structures, 6,7 and as ballistic-penetration resistant metallic armor. 8 The inherent microstructure of polyurea comprise of two distinct types of domains: "hard" realms formed by hydrogen bonded polar urea linkages (ANHACOANHA) and "soft" domains, consisting of long aliphatic polyether chains.…”
Section: Introductionmentioning
confidence: 99%
“…Certain products, i.e., pipes, freight wagon liners, industrial floors, need to be brought back to service as soon as possible, and in such cases, the fast curing nature of polyurea is extremely beneficial. Polyurea is also entering into areas like personnel‐protective gear, retrofits for unreinforced structures, and as ballistic‐penetration resistant metallic armor, where rapid curing has enormous advantages.…”
Section: Introductionmentioning
confidence: 99%